PENGAKTUALAN UNSUR MITOLOGI DALAM PUlSl GOENAWAN MOHAMAD DAN SAPARDI DJOKO DAMONO*) - Burhan Nurgiyantoro Burhan Nurgiyantoro (LPMPP Universitas Negeri Yogyakarta, 1999)
lndoiiesiaii literary writing today appears to containconsi-derable adoption and actualization of mythologicalstories coming fiom various parts of the country and fiomabroad. Goenawan Mo-hammad and Sapardi Djoko Damonoare the foremost Indonesian poets now considered 'pioneers